11x-4*(100+x)=48

Simple and best practice solution for 11x-4*(100+x)=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-4*(100+x)=48 equation:


Simplifying
11x + -4(100 + x) = 48
11x + (100 * -4 + x * -4) = 48
11x + (-400 + -4x) = 48

Reorder the terms:
-400 + 11x + -4x = 48

Combine like terms: 11x + -4x = 7x
-400 + 7x = 48

Solving
-400 + 7x = 48

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '400' to each side of the equation.
-400 + 400 + 7x = 48 + 400

Combine like terms: -400 + 400 = 0
0 + 7x = 48 + 400
7x = 48 + 400

Combine like terms: 48 + 400 = 448
7x = 448

Divide each side by '7'.
x = 64

Simplifying
x = 64

See similar equations:

| 3+5logx=18 | | X^2-kx+29=0 | | -25x^7-5x^6= | | x^4+3=8x^2 | | 3(2x-3)=-6x+9 | | -4x^2+20x+25=125 | | -4x^2+20x-100=0 | | x^3+6=x(2x+3) | | 2z^2-9z+4=0 | | 1/7(28-3a) | | 2+4+x=1+5 | | (x+2x-10)/10-2y=3/4y-(4-3y)+x | | 560-.6y+y=600 | | Y=14x-7 | | 0.33x-3=0 | | 5600=10x+6y | | 0.3x-3=0 | | -2x+5=-x | | 7x-4(3x+4)=9 | | -8x+23=-9x-1-3x | | 2x+4=-9x-7 | | 6+8(x-2)=6(x+2) | | 4k-7=19 | | -7/-2=14 | | 4x^2+4x+2x^2+3y= | | 5x-7=5-(2x-9) | | 2(t)=-0.8t^2+24t+8 | | 9(x+8)=5(3x-6) | | 7/8/5/18 | | 8m^2+4m^2-6m^2= | | -8x+18=-6(x-4) | | 17x-4=13x+12 |

Equations solver categories